The Opportunities of Formation of Effective Functioning Social Protection System in RA - Yarmaloyan, Marine (Journal of Sociology: Bulletin of Yerevan University, 2017)
The article presents the main problems impeding the formation of effective functioning social protection system in RA. The author also suggests possible solutions to those problems